Revealing the Beauty of Early Islamic Art (The Biblical archaeology review, 2022)
After a five-year, $12 million restoration effort, one of the most elaborate and expansive mosaic floors ever discovered in the Holy Land is once again accessible to the public. First uncovered in the 1930s at the site of Khirbat al-Mafjar just north of Jericho, the nearly 9,000-square-foot mosaic adorned the floor of a large […]